La génesis de las rotaciones gimnásticas (I) - Sáez Pastor, Francisco; Gutiérrez Sánchez, Águeda (KRONOS, 2007)
This article explains gymnastic rotations on a general way, including all movements possibilities in which spin and swing are performed. A general classifi cation and a dynamic analysis of each one of them are established; each kind of rotation is demonstrated and justifi ed depending on its Biomechanical origin. These movements can not be performed spontaneously, only at gymnasts will, but technical gestures that respond to Biomechanical principles must also be generated.